KEDUDUKAN PEMIKIRAN KI HADJAR DEWANTARA DALAM FILSAFAT PENDIDIKAN - Siswadi, Gede Agus; Murtiningsih, Rr. Siti (Padma Sari: Jurnal Ilmu Pendidikan, 2024)
Ki Hadjar Dewantara is a central figure in education in Indonesia. His various thoughts were able to provide awareness to society during the Dutch colonial era, which did focus on education that was more oriented toward work skills. Ki Hadjar Dewantara through his great determination to establish an educational institution named "Taman Siswa" to restore the essence of education which gives the principle of independence. Education is also intended to help the growth and development of students so that students are active and able to realize all the competencies that exist in each individual student. This research seeks to find Ki Hadjar Dewantara's views regarding the concept of education and to see the position of Ki Hadjar Dewantara's thoughts regarding education in the structure of the philosophy of education. This study uses a qualitative method with a philosophical hermeneutic approach. The results of this study indicate that Ki Hadjar Dewantara's thoughts regarding the concept of education are more oriented toward the educational philosophy of essentialism, existentialism, progressivism, and perennials. So that in this context the idea of ​​Ki Hadjar Dewantara does not only rely on one school of educational philosophy, but is eclectic in nature, which means it combines several schools of educational philosophy which do not contradict one another but use positive principles from each school of philosophy. education and pay attention to the culture of Indonesian society.